Predator hunting modes and predator–prey space games. (15th December 2019) - Luttbeg, Barney; Hammond, John I.; Brodin, Tomas; Sih, Andrew
Abstract: Predators and prey are often engaged in a game where their expected fitnesses are affected by their relative spatial distributions. Game models generally predict that when predators and prey move at similar temporal and spatial scales that predators should distribute themselves to match the distribution of the prey's resources and that prey should be relatively uniformly distributed. These predictions should better apply to sit‐and‐pursue and sit‐and‐wait predators, who must anticipate the spatial distributions of their prey, than active predators that search for their prey. We test this with an experiment observing the spatial distributions and estimating the causes of movements between patches for Pacific tree frog tadpoles ( Pseudacris regilla ), a sit‐and‐pursue dragonfly larvae predator ( Rhionaeschna multicolor ), and an active salamander larval predator ( Ambystoma tigrinum mavortium ) when a single species was in the arena and when the prey was with one of the predators. We find that the sit‐and‐pursue predator favors patches with more of the prey's algae resources when the prey is not in the experimental arena and that the prey, when in the arena with this predator, do not favor patches with more resources. We also find that the active predator does not favor patches with more algae and that prey, when with an active predator, continue to favor these higher resource patches. These results suggest that the hunting modes of predators impact their spatial distributions and the spatial distributions of their prey, which has potential to have cascading effects on lower trophic levels. Abstract : Proportions (with SE bars) of tadpoles in the four resource patch types differing in amount of prey resource present for T, TD, and TS treatments. * indicates that the slope of number of tadpoles in a patch versus the resources in the patch significantly differed from 0.